2003
DOI: 10.6028/jres.108.017
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous calcium phosphate-based bioactive polymeric composites for mineralized tissue regeneration

Abstract: Amorphous calcium phosphate (ACP), a postulated precursor in the formation of biological hydroxyapatite, has been evaluated as a filler phase in bioactive polymeric composites that utilize dental monomers to form the matrix phase on polymerization. In addition to excellent biocompatibility, these composites provided sustained release of calcium and phosphate ions into simulated saliva milieus. In an effort to enhance the physicochemical and mechanical properties and extend the utility of remineralizing ACP com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
179
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(191 citation statements)
references
References 22 publications
6
179
0
6
Order By: Relevance
“…Skrtic et al [153][154][155] has introduced composite materials containing ACP, which release significant amount of calcium and phosphate ions. It was demonstrated that the remineralizing potential of ACP was enhanced through its hybridization with silicon or zirconium elements.…”
Section: Dental Composites With Remineralizing Actionmentioning
confidence: 99%
“…Skrtic et al [153][154][155] has introduced composite materials containing ACP, which release significant amount of calcium and phosphate ions. It was demonstrated that the remineralizing potential of ACP was enhanced through its hybridization with silicon or zirconium elements.…”
Section: Dental Composites With Remineralizing Actionmentioning
confidence: 99%
“…Changes in chemical and biological properties depend on the nature of the side group. Furthermore, the characteristics of chitosan, such as cationic, hemostatic and insoluble at high pH, can be completely reversed, which can make the anionic watersoluble molecule and also presenting anticoagulants properties [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In addition, recent studies have shown that poly(lactic-co-glycolic acid) microspheres coated with zirconium-modified amorphous calcium phosphate (Zr-ACP) promoted preosteoblast cell attachment and supported cell differentiation. 28,30 Although electrospinning provides fine control over nanofiber synthesis, there are some limitations to applications in tissue engineering such as the inability to deposit fibers without an electric field, slow deposition rates, complex synthesis setups, and poor cell penetration within a fibrous network. 13,31 As shown in this and our earlier studies, nanofiber airbrushing provides a solution to many of these limitations.…”
Section: Introductionmentioning
confidence: 99%